Penerapan Terapi Assertiveness Training dalam Asuhan Keperawatan Jiwa pada Ny.Ay dengan Masalah Risiko Perilaku Kekerasan di UPTD. Rumah Sakit Jiwa Prof.Dr. V.L. Ratumbuysang - Kaunang, Nathania; Buanasari, Andi; Usman, Suharno (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2025)
Background. Schizophrenia has common symptoms, one of which is violent behaviour. The impact of violent behaviour makes patients unable to control themselves by hurting themselves and others and even damaging the environment. Interventions for schizophrenic patients at risk of violent behavior through collaborative interventions, namely Assertiveness Training therapy encourages patients to behave well by expressing their feelings and thoughts. Objective. To make patients at risk of violent behaviour more assertive by expressing their feelings and desires and meeting their needs. Methods. This writing uses a case study design, focusing on the Assertiveness Training collaboration intervention, which consisted of 4 intervention sessions conducted over 6 days and were repeated in 2 intervention sessions. The sample in this study amounted to 1 person, namely the patient Mrs AY in the Kabela Isolation room of the RSJ, Prof. Dr V.L. Ratumbuysang. Results. There is a decrease in pre- and post-set scores, which proves that patients can act assertively. Conclusion. Patient Mrs AY's assertive behaviour increased, and several results related to the provision of assertiveness training therapy, which is used as a reference for educational purposes, prove that assertiveness training therapy has an influential success rate in reducing violent behaviour in patients.